Knowledge Of Pregnant Women About The Benefits Of Pregnancy Books In Ottawa - Raywat Deonandan (International Journal of Health Engineering and Technology, 2022)
This study was conducted using quantitative study approach with cross sectional design and the data collected is primary data obtained by distributing questionnaires. The study was conducted on pregnant women who checked their pregnancy at canal Hospital in canada. based on the results of research conducted that the utilization of pregnant women's books as much as 74.4% who utilize pregnant books, while 25.6% who do not utilize pregnant books, variables related to utilization is vaiabel family encouragement and availability of time and the most dominant is family encouragement(or=2.659). Suggestions from the authors need to strengthen maternal and child health programs by continuously evaluating the performance of health workers in socializing the importance of pregnant books for pregnant women.